A pediatric regimen for adolescents and young adults with Philadelphia chromosome‐negative acute lymphoblastic leukemia: Results of the ALLRE08 PETHEMA trial. (5th February 2020) - Ribera, Josep‐Maria; Morgades, Mireia; Montesinos, Pau; Tormo, Mar; Martínez‐Carballeira, Daniel; González‐Campos, José; Gil, Cristina; Barba, Pere; García‐Boyero, Raimundo; Coll, Rosa; Pedreño, María; Ribera, Jordi; et al.
Abstract: Background: Pediatric‐based or ‐inspired trials have improved the prognosis of adolescents and young adults (AYA) with Philadelphia chromosome‐negative (Ph‐neg) acute lymphoblastic leukemia (ALL). Methods: This study reports the results of treatment of the ALLRE08 trial, a full pediatric trial for AYA aged 15‐30 years with standard‐risk (SR) ALL. Results: From 2008 to 2018, 89 patients (38 adolescents [15‐18 years] and 51 young adults [YA, 19‐30 years], median age: 20 [15‐29] years) were enrolled in the ALLRE08 trial. The complete response (CR) was 95%. Twenty‐two patients were transferred to a high‐risk (HR) protocol because of poor marrow response on day 14 ( n  = 20) or high‐level of end‐induction minimal residual response (MRD ≥ 0.25%, n  = 2). Cumulative incidence of relapse (CIR) at 5 years was 35% (95%CI: 23%‐47%), with significant differences between adolescents and YA: 13% (4%‐28%) vs 52% (34%‐67%), P  = .012. No treatment‐related mortality was observed in 66/66 patients following the ALLRE08 trial vs 3/23 patients moved to a HR trial. The estimated 5‐year overall survival (OS) was 74% (95%CI: 63%‐85%), with significantly higher rates for adolescents vs YA: 87% (95%CI: 74%‐100%) vs 63% (46%‐80%), P  = .021. Although CIR or OS were lower in patients who were transferred to a HR trial, the differences were not statistically significant (CIR: 34% [21%‐47%] vs 37% [14%‐61%]; OS: 78% [66%‐90%] vs 61% [31%;91%]). Conclusion: A full pediatric trial is feasible and effective for AYA with Ph‐neg, SR‐ALL, with better results for adolescents than for YA. Outcome of patients with poor early response rescued with a HR trial was not significantly inferior. Abstract : A full pediatric trial is feasible and effective for adolescent and young adults with acute lymphoblastic leukemia, with better results for adolescents than for young adults. The outcome of patients showing poor early response was not significantly inferior than that observed for good responders after being transferred to a high‐risk trial.